2018
DOI: 10.1002/cam4.1747
|View full text |Cite
|
Sign up to set email alerts
|

BMI trajectories and risk of overall and grade‐specific prostate cancer: An observational cohort study among men seen for prostatic conditions

Abstract: BackgroundDynamic longitudinal patterns in body mass index (BMI) have been suggested to better predict health outcomes than static measures. Effects of BMI trajectories on prostate cancer (PCa) risk have not been thoroughly explored.MethodsCohort data were derived from electronic medical records of patients who were admitted to a tertiary‐care hospital in the Southeastern USA during 1994‐2016. Patients with a history of urologic clinic visit because of any prostatic condition and with repeatedly measured BMI (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 34 publications
2
15
0
Order By: Relevance
“…To go further in the understanding of the relation between obesity and cancer risk, it has been suggested that BMI trajectory modeling may provide a more appropriate method to study the role of obesity in cancer risk compared to static measures of BMI. 10 To the best of our knowledge, only four studies have explored the association between body shapes 11 or BMI trajectories [12][13][14] and prostate cancer incidence or mortality. One study, based on body shapes trajectories, did not find any association with advanced prostate cancer, 11 while the three studies based on BMI trajectories observed a higher risk of overall 13 or aggressive/fatal prostate cancer [12][13][14] for men progressing from normal weight to overweight or obesity, compared to men with stable normal BMI, suggesting a role of life course obesity in prostate carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To go further in the understanding of the relation between obesity and cancer risk, it has been suggested that BMI trajectory modeling may provide a more appropriate method to study the role of obesity in cancer risk compared to static measures of BMI. 10 To the best of our knowledge, only four studies have explored the association between body shapes 11 or BMI trajectories [12][13][14] and prostate cancer incidence or mortality. One study, based on body shapes trajectories, did not find any association with advanced prostate cancer, 11 while the three studies based on BMI trajectories observed a higher risk of overall 13 or aggressive/fatal prostate cancer [12][13][14] for men progressing from normal weight to overweight or obesity, compared to men with stable normal BMI, suggesting a role of life course obesity in prostate carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In the meanwhile, BMI trajectories have been suggesting to better predict health outcomes than static measures. 10 To date, only four studies were able to investigate body shapes or BMI trajectories over adulthood on prostate cancer risk, [11][12][13][14] suggesting a higher risk of overall and aggressive prostate cancer for men progressing from normal weight to overweight or obesity, compared to men with stable normal BMI.…”
mentioning
confidence: 99%
“…This method assumes that individual differences in trajectories can be summarized by a finite set of different polynomial functions of time. In the past years, this method has been successfully used to examine the association between BMI trajectories and the risk of hypertension, cancer and all‐cause mortality. However, to date, just a few studies have explored the association between BMI trajectories identified by GBTM and diabetes risk.…”
Section: Introductionmentioning
confidence: 99%
“…Body mass index (BMI) is a good index to compare comorbidities for prostate cancer [43,44]. Because there was a lack of exact BMI values in our database, BMI was unable to be considered as a comorbidity for prostate cancer in this study.…”
Section: Discussionmentioning
confidence: 99%